2003
DOI: 10.1016/s0006-3495(03)74852-8
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of ABA into Bilayers of Di-Saturated Phosphatidylcholines as Measured by DSC

Abstract: Using differential scanning calorimetry, we have investigated partitioning of the plant hormone abscisic acid into a homologous series of di-saturated phosphatidylcholines increasing in chain length from C(14) to C(19). Partition coefficients calculated from the shift in T(m) range from 1280 for DiC(14)PC to 480 for DiC(19)PC. The free energy of transfer is chain-length independent with a value of DeltaG = -17.4 kJ/mol and an enthalpic contribution of DeltaH = -22.6 kJ/mol. The low net entropic contribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
3
4
0
Order By: Relevance
“…In our study, the DSC results demonstrated a concentration-dependent change. A comparable change of the DSC thermogram has been revealed by the addition of compounds such as tocopherol [24], abscisic acid [25], cholesterol [26], and cholesterol/vinblastine [27]. A decreased main transition temperature of di-saturated palmitoyl-phosphatidyl-choline bilayer membranes has previously been found from LAs [22].…”
Section: Discussionsupporting
confidence: 54%
“…In our study, the DSC results demonstrated a concentration-dependent change. A comparable change of the DSC thermogram has been revealed by the addition of compounds such as tocopherol [24], abscisic acid [25], cholesterol [26], and cholesterol/vinblastine [27]. A decreased main transition temperature of di-saturated palmitoyl-phosphatidyl-choline bilayer membranes has previously been found from LAs [22].…”
Section: Discussionsupporting
confidence: 54%
“…Negative Δ ads S values were previously determined for adsorption of aromatic molecules such as estrone and 4-phenyl phenol to POPC lipid bilayers and for tetracaine adsorbed to SLBs composed of DOPC, DOPC + 28% CHO, and SOPC . In the current studies, adsorption of indomethacin to DOPC resulted in |Δ ads H | > | T Δ ads S | and suggests that indomethacin may behave like abscisic acid, which adsorbed to DOPC through an enthalpically driven process . Similar to the results reported here, adsorption of endocrine-disrupting chemicals from the aqueous phase to saturated, gel-phase DPPC lipids was driven by increased entropy, whereas adsorption from aqueous phase to fluid-phase lipids (DOPC and DMPC) was driven by enthalpic forces …”
Section: Resultssupporting
confidence: 88%
“…Following the precedent set in previous publications 33,53,58,77 and because K eq is not always measured at standard conditions, we use the term Δ ads G instead of Δ ads G 0 to represent the Gibbs energies determined experimentally from eq 6. For aqueousphase indomethacin adsorbed to lipid bilayers composed of DOPC at 25 °C, Δ ads G is 9.8 kJ/mol higher than the Δ ads G for the anesthetic tetracaine 9 (Δ ads G = −23.6 kJ/mol) and 16 kJ/ mol higher than the plant hormone, abscisic acid 72 (Δ ads G = −17.4 kJ/mol) adsorbed to DOPC. Indomethacin is about 1.4 times larger in molecular weight compared to that of either tetracaine or abscisic acid.…”
Section: (Supporting Information)mentioning
confidence: 84%
See 1 more Smart Citation
“…Similar results were found the COX IV peptide 49 and for several Trp derivatives 50 . In contrast, many aromatic amphiphiles have negative enthalpy changes upon binding to lipid bilayers 3,[51][52][53] . DeVido et al 54 suggest that negative enthalpic changes are generic for spontaneous binding of small molecules to ordered lipid chain phases.…”
mentioning
confidence: 99%